Yachting as one of developing niche tourism industry - Koveshnikova, Diana; Yanenko, Larisa (My University, 2016)
Yacht tourism one of the most developing niche tourism sectors around the world. Yacht tourism is a type of tourism that generally consists of yachters, yacht building industry, marinas and yachting companies. Yacht tourism allows tourists to explore new places, discovered new things, and soak them self in different cultures. Yacht tourism is well suited for people who are passionate about cruising, travelling and leading an elegant lifestyle.
Keywords: water skiing; yacht vacations; yacht tourism; yachting; scuba diving; відпочинок на яхті; яхтний туризм; підводне плавання; катання на водних лижах; отдых на яхте; яхтный туризм; подводное плавание; водные лыжи; кафедра іноземних мов професійного спрямування